Service model based on lean manufacturing, MRP and mps to increase the level of service in a MYPE in the textile sector - Franco Goyzueta, Gonzalo Antonio (2025)
This scientific article focuses on addressing the problems related to the level of service in the textile sector of MYPES. A comprehensive study was carried out based on 40 articles published between 2018 and 2022, using the Scopus database and relevant keywords. The results revealed several problem cases, which were addressed through the implementation of lean manufacturing tools, such as 5S, work standardization and SMED, along with the use of MRP and MPS. These tools will be applied with the objective of improving the level of service, evaluating the percentage of improvement obtained through its implementation. In addition, solutions were proposed to optimize the supply of raw material, strengthen quality controls and properly calibrate the machinery. This study offers a valuable perspective and provides a solid starting point to improve the level of service in the textile sector of MYPES, thus contributing to the advancement and development of the industry.